Influence of Fluid Film Bearings with Different Axial Groove Shapes on Automotive Turbochargers: An Experimental Study - Luiz Henrique Jorge Machado; Oscar Ricardo Sandoval; José Victor Matos Carvalho Pereira; Juliana Primo Basílio de Souza; Bryan Castro Caetano; Vítor Mourão Hanriot; Fabrício José Pacheco Pujatti; Marco Tulio Correa de Faria (Lubricants, 2022)
Most commercial automotive turbochargers (TC) employ semi-floating ring bearings (SFRB) with axial groove shapes. In order to bring some insights into the role played by the axial groove geometry on the dynamics of TC, this work deals with an experimental study of the rotordynamic behavior of a stock automotive turbocharger operating on SFRB with two different groove shapes, which have the same volume and width, and with the same number of grooves. The rotating machine behavior has been evaluated under different operating conditions using a test bench specially designed to analyze turbochargers. Rotordynamic (RD) characteristics of automotive turbochargers are estimated to evaluate the influence of the axial groove geometry on the machine vibratory behavior. Frequency spectra and orbital plots of the rotor are obtained from accelerometers and proximity probes mounted on the turbocharger. The comparative analysis of the vibrational behavior of automotive turbochargers running on different supporting systems allows the identification of the role played by the axial grooves on the machine rotordynamic performance. The experimental results rendered in this work permit to classify the influence of the axial groove geometry on the turbocharger rotordynamic behavior for several speed and flow conditions.